Seahorse Hydrolisate (Hippocampus kuda) and Anti-Inflammatory Activity Test with Protein Denaturation Inhibition Method - Nur Azizah Nasution; Mala Nurilmala; Asadatun Abdullah (Jurnal Perikanan Universitas Gadjah Mada, 2019)
Seahorse is marine biota that have commercial value and used as ornamental fish and traditional medicinal ingredients. Utilization of seahorses has still not been extensively studied, especially in the form of hydrolysates. Hydrolysates of seahorses are known to have efficacy in biological activity. This study was conducted to identify seahorse morphometrics, determine selected enzymes based on the degree of hydrolysis and determine the anti-inflammatory activity of hydrolysates. The results showed that morphometric identification showed morphological characteristics of Hippocampus kuda, namely the number of body rings 12 units, tail ring 35 units, eye protrusion and cheeks as much as 1 unit, average head length of 3.5 cm, number of body rings on dorsal fin 3 units. The best degree of hydrolysis of seahorses is protein hydrolysis using alkalase enzyme of 42.49%. The highest anti-inflammatory activity on sea horse hydrolyzate has %inhibition of 42.88%.